Volume 13 - Anderson, A. (International Journal of Psychosocial Rehabilitation, 2009)
This professional peer reviewed publication and data archive is dedicated to the enhancement of program development, evaluation and innovations in mental health and substance abuse treatment programs worldwide. Its goal is to provide a public forum for practitioners, consumers and researchers to address the multiple service needs of patients and families and help determine what works, for whom under a variety of circumstance